Serological And Cytokine Profiling of Umbilical Cord Blood for Maternal Torch Infections: A Cross-Sectional Study on Neonatal Risk in Yaoundé, Cameroon - Touangnou-Chamda, Sabine Aimée; Bikoï, Jacky Njiki; Netongo, Palmer Masumbe; Sake, Carole Stephanie; Batoum, Véronique Mboua; Membangbi, Alexandra Emmanuelle; Kwedjeu, Cassandre; Mikangue, Chris André Mbongue; Nguiffo, Elsa Makue; Boda, Maurice; et al. (British Journal of Healthcare and Medical Research, 2026)
Background: Umbilical cord blood (UCB) represents a valuable biological matrix for assessing neonatal exposure to maternal infections and immune status at birth. In resource-limited settings such as Cameroon, its diagnostic potential remains underutilized, particularly for the detection of vertically transmitted infections within the TORCH complex ˗ Toxoplasma gondii, Rubella virus (Rubivirus rubellae), Cytomegalovirus (CMV)/ Human Herpesvirus 5 (HHV-5), and Herpes Simplex Virus types 1 and 2 (HSV-1/2). Objectives: This study aimed to determine the seroprevalence of TORCH infections in maternal venous blood and UCB, and to compare cytokine profiles in order to characterize neonatal immune activation at birth. Methods: A cross-sectional study was conducted from June to December 2024 across two referral hospitals in Yaoundé, Cameroon. A total of 108 mother-newborn pairs were enrolled consecutively. Paired maternal venous blood and UCB samples were tested using EVANCARE IgM/IgG TORCH rapid diagnostic tests (RDT), and ELISA-based ProcartaPlex™ multiplex cytokine profiling (12 analytes). Results: TORCH seroprevalence in UCB reflected maternal infection status, with high concordance for Toxoplasma gondii (90.0%; maternal 77.5% vs. UCB 72.5%) and CMV (70.0%; maternal 55.0% vs. UCB 50.0%). Cytokine profiling revealed that 10 of 12 analytes differed between compartments; IL-6 was significantly higher in maternal plasma (33.94 vs. 25.01 pg/mL; p < 0.0001) while IL-2 was significantly elevated in UCB (17.43 vs. 16.54 pg/mL; p = 0.04), with IL-4 and IL-5 showing identical values across both compartments. Conclusion: Maternal TORCH infections exert a measurable burden on neonatal infectious and immunological status at birth. UCB represents a non-invasive and ethically advantageous specimen for neonatal assessment. These findings support the integration of TORCH screening and UCB cytokine analysis into routine antenatal care protocols in low-resource settings to reduce neonatal morbidity.